Seed micromorphology of Sedum (s.l.) from Zhejiang and its taxonomic implications - JIN Xiao-feng; QIAN Li; LU Yan-hua; ZHANG Hong-wei; WANG Hui-zhong (浙江大学学报. 农业与生命科学版)
Seeds of 26 species of Sedum (s.l.), which were collected from Zhejiang Province of China, were observed under scanning electron microscope (SEM). The systematic significance of seed micromorphology was studied. Based upon the size, shape, and surface sculpture of the seeds, five types were recognized, namely Orostachys-type, Hylotelephium-type, Phedimus-type, Filipes-type, and Sedum-type respectively. Seed micromorphology can not only easily delimitate the different genera, such as Orostachys, Hylotelephium and Phedimus, but also recognize the subdivisions within Sedum s. str., i. e. sect. Filipes and sect. Sedum. Seeds of the plants in sect. Sedum show consistency and the sculptures are even or uneven mastoid. This can be used to recognize the taxa of this section partially. Seed micromorphology indicates that sect. Filipes was a natural group within Sedum s. str., but those of the three species in Sedum ser. Bracteata were quite different from each another. Ser. Bracteata was not a natural subdivision within Sedum s. str. The results above indicate that seed micromorphology is of significant implication in the taxonomy of Sedum s.l.